Ca9Sc(PO4)7:Ce3+, Mn2+ – A Red‐Emitting Phosphor Based on Energy Transfer. Issue 6 (19th January 2016) - Li, Hai‐Feng; Jia, Yong‐Lei; Ma, Teng‐Fei; Pang, Ran; Sun, Wen‐Zhi; Li, Da; Fu, Ji‐Peng; Zhang, Su; Jiang, Li‐Hong; Li, Cheng‐Yu
Abstract: A series of novel color‐tunable phosphors, Ca9 Sc(PO4 )7 : x Ce 3+, y Mn 2+ (CSP: x Ce 3+, y Mn 2+ ), have been synthesized by traditional high‐temperature solid‐state reactions. The optical properties of CSP: x Ce 3+ and CSP:0.02Ce 3+, y Mn 2+ were systematically investigated with various spectral technologies. A phosphor with a broad, deep‐red emission, CSP:0.02Ce 3+, 0.1Mn 2+, was prepared by an energy transfer process with the CIE chromaticity coordinates (0.669, 0.307). CSP:Ce 3+, Mn 2+ phosphors excited at 254 nm display two broad emission bands: one centered at around 360 nm is assigned to the 5d 1 –4f 1 electronic transition of Ce 3+ ions, and the other at about 650 nm is attributed to the 4 T1 ( 4 G) → 6 A1 ( 6 S) transition of Mn 2+ ions. The energy transfer mechanism from Ce 3+ to Mn 2+ in the CSP:Ce 3+, Mn 2+ samples was discovered to be the dipole–dipole interaction, which was confirmed by the estimated critical distance between Ce 3+ and Mn 2+ (13.0 Å) by the spectral overlap method. Furthermore, the higher thermal stability of CSP:Ce 3+, Mn 2+ makes it feasible for a potential application in white‐light‐emitting diodes (WLEDs). Abstract : A phosphor with a broad, deep‐red emission, Ca9 Sc(PO4 )7 :0.02Ce 3+, 0.1Mn 2+ (CSP:0.02Ce 3+, 0.1Mn 2+ ), was prepared by energy transfer from Ce 3+ to Mn 2+ through a dipole–dipole interaction. CSP:Ce 3+, Mn 2+ phosphors excited at 254 nm emit light in two bands: one at around 360 nm, assigned to the 5d 1 –4f 1 transition of Ce 3+, and the other at about 650 nm, derived from the 4 T1 ( 4 G) → 6 A1 ( 6 S) transition of Mn 2+ .